An analysis of the liability rule in Latvia in case of a transfer of an undertaking in the context of freedom of contract principle - Šļujeva, Kristīne (Riga Graduate School of Law, 2018)
The objective of this Thesis is to answer whether Article 20 of the Commercial Law of Latvia is compatible with freedom of contract principle. Chapter 1 analyzes the limitation put on freedom of contract principle in case of a transfer of an undertaking set in Article 20 and the purpose of such limitation. Chapter 2 analyzes the way freedom of contract principle manifests in contemporary legal framework, both in Latvian normative acts and European Contract Law. Thesis concludes that Article 20 is incompatible with freedom of contract principle. Considering that freedom of contract, while a component of fundamental, is not an absolute right, the existence of the limitation on freedom of contract principle in Article 20 does not itself make Article 20 incompatible with freedom of contract principle.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Private law::Commercial and company law; Latvia; Contract law